Spatial Changes of Land Use Using Landsat Data in Banjir Kanal Timur Watershed Semarang City - Azzahra, Arrum; Andawayanti, Ussy; Suhartanto, Ery (Fakultas Teknik, Universitas Brawijaya, 2026)
This study analyzes land use and land cover (LULC) changes in the Banjir Kanal Timur Watershed, Semarang City, from 2004 to 2024, utilizing multi-temporal Landsat data and GIS-based supervised classification methods. This research focuses on a medium-sized tropical coastal city in Indonesia that has received little attention in previous LULC studies, particularly over a two-decade period. The East Flood Canal was selected because of its strategic role and vulnerability to unregulated land-use change, making it an ideal case study to assess the impacts of urban sprawl. The primary objective is to assess the extent of urban growth and its effects on natural land cover, particularly forested areas, water bodies, and brushwood. Using Landsat 7, 8, and 9 satellite imagery, this study applied supervised classification to categorize land cover types and evaluate spatial changes over time. The results indicate a substantial increase in urban and built-up land, from 49.63% in 2004 to 80.57% in 2024, accompanied by a drastic decline in forest cover, from 40.69% to 12.13%, highlighting rapid urbanization and environmental degradation. The classification reliability was validated using a confusion matrix, with overall accuracy exceeding 90% and Kappa statistics ranging from 0.852 to 0.869, indicating substantial to almost perfect agreement. These findings underscore the urgent need for sustainable urban planning, as continued land conversion may lead to increased flood risks, biodiversity loss, and reduced water retention capacity. This research demonstrates the effectiveness of remote sensing in monitoring land use dynamics and offers vital insights for policymakers to create balanced strategies between development and environmental preservation in Semarang City.